Transcriptome Profiling Reveals the Endogenous Sponging Role of LINC00659 and UST-AS1 in High-Altitude Induced Thrombosis - Jha, Prabhash Kumar; Vijay, Aatira; Prabhakar, Amit; Chatterjee, Tathagata; Nair, Velu; Bajaj, Nitin; Kumar, Bhuvnesh; Sharma, Manish; Ashraf, Mohammad Zahid (Thrombosis and Haemostasis, 2021)
Background The pathophysiology of deep vein thrombosis (DVT) is considered as multifactorial, where thrombus formation is an interplay of genetic and acquired risk factors. Little is known about the expression profile and roles of long noncoding RNAs (lncRNAs) in human subjects developing DVT at high altitude.Methods Using RNAseQ, we compared peripheral blood mRNA and lncRNA expression profile in human high-altitude DVT (HA-DVT) patients with high-altitude control subjects. We used DESeq to identify differentially expressed (DE) genes. We annotated the lncRNAs using NONCODE 3.0 database. In silico putative lncRNA–miRNA association study unravels the endogenous miRNA sponge associated with our candidate lncRNAs. These findings were validated by small-interfering RNA (siRNA) knockdown assay of the candidate lncRNAs conducted in primary endothelial cells.Results We identified 1,524 DE mRNAs and 973 DE lncRNAs. Co-expressed protein-coding gene analysis resulted in a list of 722 co-expressed protein-coding genes with a Pearson correlation coefficients >0.7. The functional annotation of co-expressed genes and putative proteins revealed their involvement in the hypoxia, immune response, and coagulation cascade. Through its miRNA response elements to compete for miR-143 and miR-15, lncRNA-LINC00659 and UXT-AS1 regulate the expression of prothrombotic genes. Furthermore, in vitro RNA interference (siRNA) simultaneously suppressed lncRNAs and target gene mRNA level.Conclusion This transcriptome profile describes novel potential mechanisms of interaction between lncRNAs, the coding genes, miRNAs, and regulatory transcription factors that define the thrombotic signature and may be used in establishing lncRNAs as a biomarker in HA-DVT.
Keywords: long noncoding RNA; thrombosis; hypoxia; high altitude